The Effect of Gender on Algebra Achievement: The Meta-Analysis of Trends in International Mathematics and Science Study (TIMSS) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In this meta-analysis study; the effect of gender on algebra achievement was tested in the context of TIMSS. The study was carried out in two stages: (i) finding out the average effect size of gender on algebra achievement, and (ii) determining the moderators that may affect the average effect size. TIMSS 1995, 1999, 2003, 2007, 2011 and 2015 were combined and a sample of 1.202.847 people was obtained. In the study, the average effect size was calculated using the differences between means (Cohen d) based on the random effect model, whereas the significance of the moderator variables was calculated using Q statistic. The results of the study showed that gender had a low effect on achievement. In addition, the national culture, and the year of the study variables play moderator role regarding the effect of gender on achievement.